Toxicity and Microbial Degradation of Nitrobenzene, Monochloronitrobenzenes, Polynitrobenzenes, and Pentachloronitrobenzene - Pankaj Kumar Arora; Hanhong Bae (Journal of Chemistry)
Nitrobenzene and its derivatives (NBDs) are highly toxic compounds that have been released into the environment by anthropogenic activities. Many bacteria and fungi have been well-characterized for their ability to degrade NBDs. The biochemical and molecular characterization of the microbial degradation of NBDs has also been studied. In this review, we have summarized the toxicity and degradation profiles of nitrobenzene, monochloronitrobenzenes, polynitrobenzenes, and pentachloronitrobenzene. This review will increase our current understanding of toxicity and microbial degradation of NBDs.